FACTORS ASSOCIATED WITH TYPE 2 DIABETES MELLITUS AT ADAM MALIK GENERAL HOSPITAL, MEDAN, INDONESIA: Faktor yang Berhubungan dengan Diabetes Melitus Tipe 2 di RSUP Adam Malik, Medan, Indonesia - Memo Nababan; Chatarina Umbul Wahyuni; Fazidah Aguslina Siregar (Universitas Airlangga, 2023)
Background: Diabetes mellitus is third highest cause of death in Indonesia with percentage 6.71%, and 2018 Indonesia was ranked seventh among the 10 countries with most diabetes with prevalence based on blood sugar level test results 8.56%. Adam Malik General Hospital is one of the hospitals with the highest percentage of diabetes in Medan with the cases reported by 1,323 people in 2020. Purpose: This study aimed to analyze the factors related to the incidence of diabetes at the Adam Malik General Hospital. Methods: This was a cross-sectional analytical design study. The study was conducted at Adam Malik General Hospital between April 22-May 4, 2021. The population of this study included all patients who went to internal medicine, while the sample part of the population (99 respondents) was sampled accidentally. The research instruments used were questionnaires, and data collection used primary and secondary data. Data were analyzed using the chi-square test. Results: Three variables were related to the incidence of DM at Adam Malik General Hospital: family history of DM (P =0.00; PR=3.03; 95% CI= <1.37 PR <2.73), physical activity (P =0.00; PR= 3.33; 95% CI= <1.59 PR <6.95), and age (P =0.00; PR= 0.19; 95%CI= <0.52, PR <0.71). Conclusion: This study is that there are three factors related to occurrence of diabetes, namely family history, physical activity, and age. It is necessary to carry out regular physical activity every day and conduct health checks, especially for those who have a family history of DM.